In situ measurement of perfluoroalkyl substances in aquatic systems using diffusive gradients in thin-films technique. (1st November 2018) - Guan, Dong-Xing; Li, Ya-Qing; Yu, Nan-Yang; Yu, Guang-Hui; Wei, Si; Zhang, Hao; Davison, William; Cui, Xin-Yi; Ma, Lena Q.; Luo, Jun
Abstract: To better understand the environmental impact of ubiquitous perfluoroalkyl substances (PFASs) in waters, reliable and robust measurement techniques are needed. As one of the most widely used passive sampling approaches, diffusive gradients in thin-films (DGT) is not only easy to handle but also provides time-weighted analyte concentrations. Based on DGT with XAD18 as a binding agent, we developed a new methodology to measure two frequently detected PFASs in surface waters and wastewaters, i.e. perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS). Their diffusion coefficients in the diffusive gel, measured using an independent diffusion cell, were 4.37 × 10 −6 and 5.08 × 10 −6 cm 2 s −1 at 25 °C, respectively. DGT had a high capacity for PFOA and PFOS at 196 and 246 μg per gel disk, suggesting the DGT sampler was suitable for deployment of several weeks. Time-integrated concentrations of PFOA and PFOS in a natural lake and river, and a municipal wastewater treatment plant effluent using DGT samplers deployed in situ for 12–33 d were comparable to those measured by a solid-phase extraction method coupled with high-frequency grab sampling. This study demonstrates that DGT is an effective tool for in situ monitoring of PFASs in natural waters and wastewaters. Graphical abstract: Image 1 Highlights: Perfluoroalkyl substances (PFASs) in waters were detected using DGT. Diffusion coefficients of PFASs in the agarose diffusive gel were measured. DGT had a high capacity for PFASs and is suitable for deployment of several weeks. DGT is an effective tool for monitoring of PFASs in natural waters and wastewaters.